2015
DOI: 10.1007/s10517-015-2794-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Nanosized Diamond Particles on Macrophages

Abstract: The effects of synthetic diamond nanoparticles (4-6 nm) on mouse macrophage biotropism and biocompatibility and the modulation of the macrophage functions (expression of IL-1α, TNF-α, GM-CSF, bFGF, and TGF-β) by nanoparticles in different concentrations were studied in vitro during exposure of different duration. Macrophage endocytosis of nanodiamonds increased with increasing the concentration of nanoparticles in culture and incubation time. Nanodiamonds exhibited high biotropism and biocompatibility towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The medical use of NDs is probable because of their low cytotoxicity and high biological activity [9]. Several authors have reported a lack of toxic effects that manifest in the forms of inflammation and activation of macrophages [10], and symptoms of systemic toxicity after ND treatment in rats [11,12], but have also noted uptake and intracellular accumulation of NDs [13], activation of cell death (both apoptotic and necrotic) [14], and redox homeostasis disorders [15]. Diamond nanoparticles were also tested for their application in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The medical use of NDs is probable because of their low cytotoxicity and high biological activity [9]. Several authors have reported a lack of toxic effects that manifest in the forms of inflammation and activation of macrophages [10], and symptoms of systemic toxicity after ND treatment in rats [11,12], but have also noted uptake and intracellular accumulation of NDs [13], activation of cell death (both apoptotic and necrotic) [14], and redox homeostasis disorders [15]. Diamond nanoparticles were also tested for their application in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that MP endocytosis of ND increased with increase of ND concentration in culture and with prolongation of incubation [7]. Secretion of the studied enzymes increased mainly after 48 h of MP culturing in medium with ND (Table 3).…”
Section: Resultsmentioning
confidence: 57%
“…The effects of ND on the expression of cathepsins B and D and of MMP-1 and MMP-9 were studied 1, 3, 24, and 48 h after addition of ND to primary 24-h MP cultures. Sterile suspension of ND (1.6%) in bidistilled water was added to culture medium to the fi nal concentration of 20 μg/ml, after which the suspension was thoroughly mixed and subjected to ultrasonic treatment on a MUZA-0.1/22-M ultrasonic disintegrator for 10 sec at 75 W in order to prevent ND aggregation [7]. According to our data and other data, ND in a concentration of 20 μg/ml cause no cytotoxic effects on some cells, including MP, in vitro [7,9,10,11].…”
Section: Methodsmentioning
confidence: 99%
“…SCs and regenerated nerves in ND bridges showed lower proinflammatory markers, such as TNF-α and IL-6, and higher anti-inflammatory cues, such as CD206 and IL-10, than their PCL counterparts. Previous reports also showed that NDs at 10-20 μg ml −1 could stimulate transforming growth factor β and granulocyte-macrophage colony stimulating factor activation and decrease IL-1α and TNF-α expression, thus regulating the immune response in the microenvironment 35 . In addition, we analyzed STAT-3 (M2 phenotyperelated signaling protein) and NF-κB (M1 phenotyperelated signaling protein) expression 36 .…”
Section: Discussionmentioning
confidence: 92%